Curcumin inhibits lymphangiogenesis in vitro and in vivo. Issue 12 (16th September 2015) - Wang, Weicang; Sukamtoh, Elvira; Xiao, Hang; Zhang, Guodong
Abstract : Scope: Curcumin, a dietary compound from turmeric, has potent antimetastatic effects; however, the underlying mechanisms are not well understood. The aim of this study is to investigate the effects and mechanisms of curcumin on lymphangiogenesis (formation of new lymphatic vessels), which plays a critical role in tumor metastasis. Methods and results: Curcumin inhibited vascular endothelial growth factor‐C (VEGF‐C) induced lymphangiogenesis in a Matrigel plug assay in mice, and VEGF‐C induced tube formation in human dermal lymphatic endothelial cells, demonstrating its antilymphangiogenic action in vivo and in vitro. Curcumin inhibited lymphangiogenesis, in part through suppression of proliferation, cell‐cycle progression and migration of lymphatic endothelial cells, while it had little effect on matrix metalloproteinase activities. Curcumin inhibited expressions of VEGF receptors (VEGFR2 and VEGFR3), as well as downstream signaling such as phosphorylation of ERK and FAK. Finally, curcumin sulfate and curcumin glucuronide, which are two major metabolites of curcumin in vivo, had little inhibitory effect on proliferation of human dermal lymphatic endothelial cells. Conclusion: Our results demonstrate that curcumin inhibits lymphangiogenesis in vitro and in vivo, which could contribute to the antimetastatic effects of curcumin.